Students’ Pronunciation Problems in Pronouncing English Fricative Consonants: (An Error Analysis of Ketapang Malay Students of English Education Study Program in Academic Year 2020/2021) - Noven Armelia; Clarry Sada; Ikhsanudin (Journal of Scientific Research, Education, and Technology (JSRET), 2024)
This research aims to determine the error level of Ketapang Malay students in the English Education Department in pronouncing eight English fricative consonants and the dominant errors produced. Data were collected through performance tests using qualitative descriptive methodology. There were eight sentences in the text with 24 fricative consonants divided into initial, medial, and final positions, with the total transcriptions are 168 words. The findings showed that of the seven students, the pronunciation error was 52.38%. Based on this point, the students' error level is ''Fair”. The dominant errors occurred in labiodental voiced fricative [v] and interdental voiced fricative [ð]. The students scored poorly for these consonants because they substituted the sound with bilabial stop [p], labiodental fricative [f], alveolar stop [d], and alveolar stop [t]. In conclusion, this researcher underlined the error is caused by unfamiliarity with the sound itself.  The absence of some fricative consonant sounds in Ketapang Malay is also a major problem and the influence of spelling and pronunciation between the L1 and L2 also causes students to make errors because students tend to substitute with sounds that are easier to pronounce.